Novel Role of JAC1 in Influencing Photosynthesis, Stomatal Conductance, and Photooxidative Stress Signalling Pathway in Arabidopsis thaliana - Weronika Czarnocka; Weronika Czarnocka; Anna Rusaczonek; Anna Rusaczonek; Patrick Willems; Patrick Willems; Marzena Sujkowska-Rybkowska; Frank Van Breusegem; Frank Van Breusegem; Stanisław Karpiński (Frontiers in Plant Science, 2020)
Regulation of light absorption under variable light conditions is essential to optimize photosynthetic and acclimatory processes in plants. Light energy absorbed in excess has a damaging effect on chloroplasts and can lead to cell death. Therefore, plants have evolved protective mechanisms against excess excitation energy that include chloroplast accumulation and avoidance responses. One of the proteins involved in facilitating chloroplast movements in Arabidopsis thaliana is the J domain-containing protein required for chloroplast accumulation response 1 (JAC1). The function of JAC1 relates to the chloroplast actin filaments appearance and disappearance. So far, the role of JAC1 was studied mainly in terms of chloroplasts photorelocation. Here, we demonstrate that the function of JAC1 is more complex, since it influences the composition of photosynthetic pigments, the efficiency of photosynthesis, and the CO2 uptake rate. JAC1 has positive effect on water use efficiency (WUE) by reducing stomatal aperture and water vapor conductance. Importantly, we show that the stomatal aperture regulation is genetically coupled with JAC1 activity. In addition, our data demonstrate that JAC1 is involved in the fine-tuning of H2O2 foliar levels, antioxidant enzymes activities and cell death after UV-C photooxidative stress. This work uncovers a novel function for JAC1 in affecting photosynthesis, CO2 uptake, and photooxidative stress responses.